In situ characterization of immiscible three-phase flow at the pore scale for a water-wet carbonate rock. (November 2018) - Scanziani, Alessio; Singh, Kamaljit; Bultreys, Tom; Bijeljic, Branko; Blunt, Martin J.
Highlights: We obtained micro scale three-dimensional images of three-phase flow in situ at high temperature and pressure in a water-wet carbonate rock. Pore occupancy is quantified: brine, oil and gas occupy the centre of respectively small, intermediate and large pores. Double drainage and double imbibition are visualized in three-dimensions. Spreading oil layers and water wetting layers are observed and their thickness allows for effective flow. Wettability and the formation of oil layers favour trapping of gas over oil when the three phases are simultaneously present in the pore space. Abstract: X-ray micro-tomography is used to image the pore-scale configurations of fluid in a rock saturated with three phases - brine, oil and gas - mimicking a subsurface reservoir, at high pressure and temperature. We determine pore occupancy during a displacement sequence that involves waterflooding, gas injection and water re-injection. In the water-wet sample considered, brine occupied the smallest pores, gas the biggest, while oil occupied pores of intermediate size and is displaced by both water and gas. Double displacement events have been observed, where gas displaces oil that displaces water or vice versa. The thickness of water and oil layers have been quantified, as have the contact angles between gas and oil, and oil and water. These results are used to explain the nature of trapping in three-phase flow, specifically how oil preferentially traps gas in the presence of water.